Blood Glucose Lowering Efficacy of Strawberry Extracts Rich in Ellagitannins with Different Degree of Polymerization in Rats - Juśkiewicz Jerzy; Jurgonski Adam; Kołodziejczyk Krzysztof; Kosmala Monika; Milala Joanna; Zduńczyk Zenon; Fotschki Bartosz; Żary-Sikorska Ewa (Polish Journal of Food and Nutrition Sciences)
In two experiments on rats it was analyzed whether the lowering rate of postprandial glycaemia depends on the degree of polymerization of strawberry ellagitannins (ET). Two types of highly-concentrated polyphenolic extracts were used, one rich in monomeric ET (ETM; 94.9% polyphenols and 67% ETM in it), the second in dimeric ET (ETD; 95.9% polyphenols, and 78.0% ETD in it). The experiment 1 comprised three oral sugar tolerance tests, GTT (with glucose; to examine monosaccharide transport across epithelium), SuTT (with sucrose; to examine the activity of mucosal disaccharidase) and StTT (with starch; to examine the action of salivary alpha-amylase, and then of pancreatic amylase in the small intestine as well as all the aforementioned mechanisms), while in the experiment 2 the healthy and pre-diabetic rats were subjected to 1-h small intestine perfusion with fluids containing glucose or sucrose. Considering the shape of blood glucose concentration curve following GTT and SuTT, as well as changes in glycaemia and mucosal disaccharidases activity observed within and after small intestine perfusion, the ETM (vs. ETD) extract more positively mitigated sugar-induced post-prandial glycaemic load. Contrary to expectations, the effect of extracts on pre-diabetic rats was negligible. The extract ETD, in turn, potently mitigated starch-induced postprandial glycaemic load during test StTT. The results clearly showed that the separate mechanisms (glucose transport across the intestine, intestinal mucosal disaccharidases inhibition activity, pancreatic α-amylase inhibitory activity) leading to decreased postprandial glycaemia upon dietary administration of strawberry ellagitannins largely depended on their chemical structure, i.e. degree of polymerization.